Implementation of Website-Based Learning Media to Improve Physics Learning Outcomes - Ilmi, Muhammad Rasikh; Nurhayati, Nurhayati; Rukman, Aprilia Ruita (Universitas Negeri Makassar, 2024)
Abstract. This research aims to determine the Physics learning outcomes of class XI MIPA students at SMAN 3 Majene for the 2023/2024 academic year, through the use of website-based learning media. This is based on the diagnosis results that the physics learning outcomes of students in this class are low. This research is classroom action research with a model design according to Coghlan's opinion with the steps: 1) Diagnosis; 2) Planning actions; 3) Take action; and 4) Evaluate actions. This research consisted of two cycles, the subjects in this research were class XI MIPA 1 students, totaling 23 people. Based on the results of descriptive analysis, information was obtained that the average learning outcome of students in the initial condition was 60. After learning cycle I the average learning outcome of students was 73 and in cycle II it was 83. These results indicate that the use of website-based learning media can improve physics learning outcomes for class XI MIPA 1 students at SMAN 3 Majene. Keywords: Website Based Learning, Physics Learning Results, SMAN 3 Majene